Вплив ідей Канта на формування природничо-наукової гіпотези простору - Кадикало, Андрій; Kadykalo, Andrii (Lviv Politechnic Publishing House, 2017)
Розглянуто еволюцію та трансформацію уявлень про простір у філософії Канта. Пояснено причини відмови Канта від уявлень про абсолютний простір. За допомогою герменевтичного методу зроблено висновок, що внесок Канта сприяв розвитку наукових теорій про простір у природничих науках, зокрема мав вплив на концепції Гемгольца, Пуанкаре та інших.

The author considers evolution and transformation definition of space in Kant’s philosophy. Kant’s conception of space had a big and important influence on natural scientific knowledge. I emphasize that Kant’s conception of space has been changed. In the beginning of his scientific career, Kant was considered space as absolutely and objective. It is almost the same as Isaac Newton’s conception of space. German philosopher does think about absoluteness of space as independent from human perception. The article explains that objective space has itself parameters—move and orderliness. Kant’s idea about the move of space was very progressive and modern for his epoch. Kant does not explain absolutely space. He assumed that space is evidently in perception that makes you believe that something is true or exists. However, in secondperiod German philosopher changed his opinion: Kant is going to prove that space is objective and independent of human perception. The author explains: that Kant could not do that. Kant understood this problem and existence of the reason of this complexity. He discovered that definition of space must have marks, physical things or body, matter. Kant discovered the idea that human knows about space with help of the pure contemplation. Pure contemplation is out of limits of reason or sense – Kant’s conclusion. The article examines evolution Kant’s idea about space after him. Physical body and their motion were important in Helmholtz’s conception. His conception was coalescence natural science and psychology. It is part of psychology which had Kantian’s basis. Finally, French scientist and philosopher Henri Poincare assume about relativity and passive of space. The general conclusion of this article is that Kant got closer geometry and physics, imaginary and actually.
Kant’s ideas and their influence on the formation of natural and scientific hypothesis of the space
Keywords: простір; об’єкт; рух; чистий розум; чуття; space; object; motion; pure reason; sense; 113/119; 165